2019
DOI: 10.1039/c9ra06328e
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nickel-free graphene/porphyrin rings for photodegradation of emerging pollutants in water

Abstract: A novel hybrid photoactive material based on graphene foam (G) coupled with porphyrin-based polymers (Porph rings) was formulated by using a time-saving procedure to remove nickel from the final device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Then, the photogenerated electrons can react with O 2 and H 2 O 2 to produce ROS (OH • and HOO • ) while the holes can oxidize H 2 O in OH • or decompose H 2 O 2 into O 2 and protons (see reactions of Figure 3b). [ 45,46 ] As a confirmation, the mixed potential of ZnO:Ag micromotors is measured from Tafel plot curves under dark and UV‐light irradiation conditions. As it is possible to appreciate, under light conditions, a huge shift in the ZnO:Ag curve to more negative potentials (Δ E ZnO:Ag = 380 mV) was achieved, confirming the micromotors’ photo‐oxidation ability in water.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the photogenerated electrons can react with O 2 and H 2 O 2 to produce ROS (OH • and HOO • ) while the holes can oxidize H 2 O in OH • or decompose H 2 O 2 into O 2 and protons (see reactions of Figure 3b). [ 45,46 ] As a confirmation, the mixed potential of ZnO:Ag micromotors is measured from Tafel plot curves under dark and UV‐light irradiation conditions. As it is possible to appreciate, under light conditions, a huge shift in the ZnO:Ag curve to more negative potentials (Δ E ZnO:Ag = 380 mV) was achieved, confirming the micromotors’ photo‐oxidation ability in water.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, despite this polymer being widely used in cosmetics, its harmfulness at higher molecular weights is controversial. [ 69 ] To favor PEG capture by microrobots, their electrostatic attraction has been intensified. The pH‐dependence of microrobot Zeta potential was explored, indicating the acidic environment (pH 3) as the optimal one, microrobots being positively charged and PEG negatively charged (Figure 3c).…”
Section: Strategies For Nano/microplastics Capture and Degradation By...mentioning
confidence: 99%
“…This metal is indeed a common allergen, harmful for aquatic and human life. In order to overcome this problem, Ussia et al, in a successive work, realized a hybrid material nickel-free based on graphene and polymeric porphyrin [ 78 ]. The main difficulty of the work lied in the removal of the nickel substrate by etching it in an acid environment while avoiding the 3D graphene structure collapsing.…”
Section: Graphene/polyporphyrins Hybrid Materialsmentioning
confidence: 99%
“…In the paper, the free radical and hole scavenging tests were also performed in order to determine the individual contribution of the ROS on the photocatalytic activity of the samples. The tests revealed that the predominant species involved in the photodegradation of contaminants is the singlet oxygen [ 78 ].…”
Section: Graphene/polyporphyrins Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation